Regulator of G-Protein Signaling 4 (RGS4) Controls Morphine Reward by Glutamate Receptor Activation in the Nucleus Accumbens of Mouse Brain - Kim, Juhwan; Lee, Sueun; Kang, Sohi; Jeon, Tae-Il; Kang, Man-Jong; Lee, Tae-Hoon; Kim, Yong Sik; Kim, Key-Sun; Im, Heh-In; Moon, Changjong (Molecules and cells, 2018)
Crosstalk between G-protein signaling and glutamatergic transmission within the brain reward circuits is critical for long-term emotional effects (depression and anxiety), cravings, and negative withdrawal symptoms associated with opioid addiction. A previous study showed that Regulator of G-protein signaling 4 (RGS4) may be implicated in opiate action in the nucleus accumbens (NAc). However, the mechanism of the NAc-specific RGS4 actions that induce the behavioral responses to opiates remains largely unknown. The present study used a short hairpin RNA (shRNA)-mediated knock-down of RGS4 in the NAc of the mouse brain to investigate the relationship between the activation of ionotropic glutamate receptors and RGS4 in the NAc during morphine reward. Additionally, the shRNA-mediated RGS4 knock-down was implemented in NAc/striatal primary-cultured neurons to investigate the role that striatal neurons have in the morphine-induced activation of ionotropic glutamate receptors. The results of this study show that the NAc-specific knockdown of RGS4 significantly increased the behaviors associated with morphine and did so by phosphorylation of the GluR1 (Ser831) and NR2A (Tyr1325) glutamate receptors in the NAc. Furthermore, the knock-down of RGS4 enhanced the phosphorylation of the GluR1 and NR2A glutamate receptors in the primary NAc/striatal neurons during spontaneous morphine withdrawal. These findings show a novel molecular mechanism of RGS4 in glutamatergic transmission that underlies the negative symptoms associated with morphine administration.